Postponement strategies for supply chain environmental and economic sustainability: a systematic review, conceptual framework, and future research agenda - Le, Trung Hieu; Prataviera, Lorenzo Bruno; Skipworth, Heather; Ghadge, Abhijeet (Taylor & Francis, 2026)
Supply chains (SCs) are increasingly challenged to deliver greater value with fewer resources while minimising environmental impact. Postponement strategies have emerged as a potential solution to strike this balance, yet their impact on environmental sustainability beyond economic considerations remains under-examined. A systematic literature review provides a design-oriented approach combined with the Contexts, Interventions, Mechanisms, and Outcomes (CIMO) logic to deepen the understanding of the effects of postponement strategies on environmental and economic sustainability. The study reconceptualises postponement and traces its recent evolution, expanding it beyond delaying uncertainty-increasing value-adding activities to include their geographical location and the involvement of different supply chain partners. This further enabled the precise characterisation of contemporary postponement applications, leading to the development of propositions that suggest under which conditions postponement strategies may enhance or harm both the environmental and economic performances of SCs. Finally, a future research agenda is proposed to advance postponement and further support sustainable SCs.
Keywords: Postponement; environmental sustainability; economic sustainability; CIMO logic; conceptual framework; systematic review; 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; 12 Responsible Consumption and Production; Operations Research